Pengaruh Reward Dan Punishment Terhadap Kinerja Karyawan Dengan Disiplin Kerja Sebagai Variabel Intervening Di PT. Sinar Galesong Pratama - Kirie Stepania Ronting; Muh. Ichwan Musa; Muhammad Ilham Wardhana Haeruddin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this research is to determine the effect of reward and punishment on employee performance with work discipline as an intervening variable at PT. Sinar Galesong Pratama. The method used in this research is a quantitative approach carried out through data collection using questionnaires and data analysis. The population in this study was 102 employees, and the sampling technique in this study used saturated samples, where the entire population was sampled. The analytical method used in this research uses partial least squares (PLS). The results of the research show that there is a negative and insignificant influence of reward on work discipline, there is a positive and insignificant influence of punishment on work discipline, there is a positive and insignificant influence of work discipline on employee performance, there is a positive and significant influence of reward on employee performance, there is an influence positive and insignificant influence of punishment on employee performance, there is a negative and insignificant influence of reward on employee performance through work discipline, there is a positive and insignificant influence of punishment on employee performance.